Foliar epidermal characters and petiole anatomy of four species of Citrus L. (Rutaceae) in South-western Nigeria - Ogundare, C.S.; Saheed, S.A. (Bangladesh Journal of Plant Taxonomy, 2012)
Studies on the leaf epidermal characters and petiole anatomy of four species of Citrus L. viz., C. limon (L.) Burm., C. paradisi Macf., C. reticulata Blanco and C. sinensis (L.) Osbeck were carried out to establish and document their foliar anatomical characters with the aim of separating them from the modified varieties been cultivated globally. Leaf epidermal features that revealed close relationship among these taxa include hypostomatic condition, stomata shape and type, presence of secretory cavity on the adaxial surface, and polygonal shape of epidermal cells. The absence of secretory cavity on the abaxial surface separates C. limon and C. sinensis from others. Petiole anatomy revealed that the outline is flat without ribs in C. sinensis, convex with short ribs in C. reticulata, convex with long ribs in C. paradisi while in C. limon it is circular without ribs. Presence of trichomes and crystals distinguishes C. paradisi from the rest. DOI: http://dx.doi.org/10.3329/bjpt.v19i1.10938 Bangladesh J. Plant Taxon. 19(1): 25-31, 2012 (June)